Diagnostic and Therapeutic Endoscopic Retrograde Cholangiography Using a Short‐Type Double‐Balloon Endoscope in Patients With Altered Gastrointestinal Anatomy: A Multicenter Prospective Study in Japan. (December 2016) - Shimatani, Masaaki; Hatanaka, Hisashi; Kogure, Hirofumi; Tsutsumi, Koichiro; Kawashima, Hiroki; Hanada, Keiji; Matsuda, Tomoki; Fujita, Tomoki; Takaoka, Makoto; Yano, Tomonori; Yamada, Atsuo; Kato, Hironari; et al.
Abstract : OBJECTIVES: To evaluate the utility and safety of a short‐type double‐balloon endoscope (DBE) in the treatment of biliary disease in patients with surgically altered gastrointestinal (GI) anatomy. METHODS: This study was conducted as a multicenter, single‐arm, prospective trial at five tertiary academic care centers and three community‐based hospitals in Japan. Consecutive patients with biliary disease with altered GI anatomy were prospectively included in this study. RESULTS: A total of 311 patients underwent double‐balloon endoscopic retrograde cholangiography (ERC). The success rate of reaching the target site, the primary end point, was 97.7% (95% confidence interval (CI): 95.4–99.1). The success rate of biliary cannulation and contrast injection of the targeted duct, the secondary end point, was 96.4% (95% CI: 93.6–98.2), and the therapeutic success rate was 97.9% (95% CI: 95.4–99.2). Adverse events occurred in 33 patients (10.6%, 95% CI: 7.1–14.0) and were managed conservatively in all patients with the exception of 1 in whom a perforation developed, requiring emergency surgery. CONCLUSIONS: ERC using a short‐type DBE resulted in an excellent therapeutic success rate and a low rate of adverse events. This treatment can be a first‐line treatment for biliary disease in patients with surgically altered GI anatomy.